How to Design a Relevant Corpus for Sleepiness Detection Through Voice? - Martin, Vincent P.; Rouas, Jean-Luc; Micoulaud-Franchi, Jean-Arthur; Philip, Pierre; Krajewski, Jarek (Frontiers in Digital Health, 2021)
This article presents research on the detection of pathologies affecting speech through automatic analysis. Voice processing has indeed been used for evaluating several diseases such as Parkinson, Alzheimer or depression. If some studies present results that seem sufficient for clinical applications, this is not the case for the detection of sleepiness. Even two international challenges and the recent advent of deep learning techniques have still not managed to change this situation. This paper explore the hypothesis that the observed average performances of automatic processing find their cause in the design of the corpora. To this aim, we first discuss and refine the concept of sleepiness related to the ground-truth labels. Second, we present an in-depth study of four corpora, bringing to light the methodological choices that have been made and the underlying biases they may have induced. Finally, in light of these information, we propose guidelines for the design of new corpora.